The Influence of Political Connected Councils on Banking Performance - Omega Saputra; Supatmi (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2021)
This study aims to determine the effect of politically connected boards on banking performance as measured in accounting performance and the banking market. This study is using quantitative method with the sample of 41 banking companies listed on the IDX during 2017-2019. The dependent variable in this study is banking performance which is reflected by banking accounting performance (ROA) and banking market performance (Tobin's Q). Meanwhile, the independent variables in this study are the number of politically connected boards, both boards of directors and commissioners. The control variables are company size, leverage, and managerial ownership. The hypothesis was tested by panel data regression. The test results found that politically connected boards have no influence on banking accounting performance, while politically connected boards have a negative effect on banking market performance